Does postoperative cognitive decline after coronary bypass affect quality of life? - Frederik Keus; Fredrike Blokzijl; Michiel F Reneman; Willem Dieperink; Iwan C C van der Horst; Massimo A Mariani; Saskia Houterman; Anthony R Absalom (Open Heart)
Objective This study aimed to explore the influence of coronary artery bypass grafting (CABG) on both postoperative cognitive dysfunction and quality of life (QoL) and the association between the two patient-related outcomes.Methods In a prospective, observational cohort study, patients with elective, isolated CABG were included. Cognitive function was assessed using the Cogstate computerised cognitive test battery preoperatively, 3 days and 6 months after surgery. QoL was measured preoperatively and at 6 months using the RAND-36 questionnaire including the Physical Component Score (PCS) and the Mental Component Score (MCS). Regression analysis, with adjustment for confounders, was used to evaluate the association between postoperative cognitive dysfunction and QoL.Results A total of 142 patients were included in the study. Evidence of persistent cognitive dysfunction was observed in 33% of patients after 6 months. At 6 months, the PCS had improved in 59% and decreased in 21% of patients, and the MCS increased in 49% and decreased in 29%. Postoperative cognitive changes were not associated with QoL scores.Conclusions Postoperative cognitive dysfunction and decreased QoL are common 6 months after surgery, although cognitive function and QoL were found to have improved in many patients at 6 months of follow-up. Impaired cognitive function is not associated with impaired QoL at 6 months.Trial registration number NCT03774342.